Experimental Evaluation of Eco-friendly Light Weight Concrete with Optimal Level of Rice Husk Ash Replacement - Zareei, Seyed Alireza; Ameri, Farshad; Bahrami, Nasrollah; Dorostkar, Farzan (Salehan Institute of Higher Education, 2017)
Concrete is a versatile and cost-effective building material whose properties are influenced by age, curing condition, and installation. A number of studies deduced that there should be an association of benefits encouraged the use of partial replacements of cement seems to improve strength and durability properties of concrete. This paper presents a framework for feasibility assessment and determination of optimum percentage of rice husk ash (RHA) replacement. Five mix plans with RHA replacing ratio of 0-20% and constant micro- silica value by 10% were prepared. Tests results indicated that compressive strength increased by 20% with an increase in RHA up to 15%. The similar trend was observed in mix designs made of cement replaced by RHA up to 20% in water absorption coefficient measurement. Higher chloride ion penetration was observed in mix designs containing 25% RHA compared to that of conventional concrete. Mixes developed a slightly higher impact resistance than the control mix.